Drill Method: Creating Student Imitation Patterns In Prayer Practices - Abd. Hamid Wahid; Fathor Rozi; Abu Yazid Al Busthami (ZAHRA: Research and Tought Elementary School of Islam Journal, 2023)
This study aims to focus on the application of the drill method in forming students' imitation patterns in prayer practice. This research uses qualitative approach with Classroom Action Research. The subjects of this study were class III students MI Durrun Nafis. Validation of the research data was carried out through data triangulation, namely by using various data obtained through questionnaires, test results, and observation results. That from the drill method used by the teacher for the imitation pattern of prayer practice in class III MI Durrun Nafis students can significantly improve student skills. It is evident from movement accuracy that it experienced a increase from cycle I which obtained 76 to 97 in cycle II. While on the aspect of reading accuracy, I got 75 increased to 93 in cycle II. Furthermore, in cycle II, for student activity in praying in congregation, it became 95, which previously obtained 92. So, with this drilling method, students are trained to be actively involved in listening, responding, and demonstrating the correct movements.